2019
DOI: 10.3390/en12112218
|View full text |Cite
|
Sign up to set email alerts
|

Energy Renovation versus Demolition and Construction of a New Building—A Comparative Analysis of a Swedish Multi-Family Building

Abstract: This study addresses the life cycle costs (LCC) of energy renovation, and the demolition and construction of a new building. A comparison is made between LCC optimal energy renovations of four different building types with thermal performance, representing Swedish constructions from the 1940s, 1950s, 1960s, and 1970s, as well as the demolition of the building and construction of a new building that complies with the Swedish building code. A Swedish multi-family building from the 1960s is used as a reference bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…OPERA-MILP was developed at Linköping University, Sweden, in the 1990s to serve as a tool for identifying suitable energy renovation strategies for multifamily buildings [25]. Since then, the tool has been used in several studies of multifamily buildings [26][27][28][29] as well as historic buildings [6,30,31].…”
Section: Life Cycle Cost Optimizationmentioning
confidence: 99%
“…OPERA-MILP was developed at Linköping University, Sweden, in the 1990s to serve as a tool for identifying suitable energy renovation strategies for multifamily buildings [25]. Since then, the tool has been used in several studies of multifamily buildings [26][27][28][29] as well as historic buildings [6,30,31].…”
Section: Life Cycle Cost Optimizationmentioning
confidence: 99%
“…La Fleur et al [19] showed that the cost of the demolition and construction of a new building is higher compared to energy renovation to the same energy performance. This makes renovation the first choice, when there exists need for residences in that region.…”
Section: Introductionmentioning
confidence: 99%
“…The Committee for Climate Change in 2019 determined that a 15% reduction in domestic energy is required by 2030 to reach a net zero target in 2050 [8]. The life cycle costs in [9] show that costs are higher for demolition and rebuilding of older dwellings compared to retrofitting to the same energy standards, without even considering the obvious increase in emissions associated with demolition and rebuild, which is undesirable given the 2050 target of net zero emissions within the UK. As such, retrofitting of dwellings to upgrade them to be more energy efficient is a desirable option.…”
mentioning
confidence: 99%